2010
DOI: 10.1586/erm.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cytokine biomarkers in heart failure

Abstract: Raised levels of circulating proinflammatory cytokines are associated with disease progression and adverse outcomes in chronic heart failure patients. Inflammatory markers may be predictive of congestive heart failure and myocardial infarction, allowing enhanced risk stratification. The profile of cytokine blood levels differs in accordance with the initiating cause and type of heart failure. Therefore, subclassification of heart failure patients based on cytokine measurements could potentially identify subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…Several reports have demonstrated enhanced expression and release of inflammatory cytokines such as TNFα, IL-1, IL-6, IL-18, cardiotrophin-1 (CT-1) and Fas ligand, as well as several chemokines [e.g., monocyte chemoattractant peptide (MCP)-1/CCL2, IL-8/CXCL8, CXCL16 and CCL21 in HF patients [3,4,[7][8][9][10]18,19]. Plasma levels of these molecules appear to be elevated in direct proportion to deterioration of functional class (i.e.…”
Section: Patho-genetic Role Of Inflammation In Hfmentioning
confidence: 99%
See 4 more Smart Citations
“…Several reports have demonstrated enhanced expression and release of inflammatory cytokines such as TNFα, IL-1, IL-6, IL-18, cardiotrophin-1 (CT-1) and Fas ligand, as well as several chemokines [e.g., monocyte chemoattractant peptide (MCP)-1/CCL2, IL-8/CXCL8, CXCL16 and CCL21 in HF patients [3,4,[7][8][9][10]18,19]. Plasma levels of these molecules appear to be elevated in direct proportion to deterioration of functional class (i.e.…”
Section: Patho-genetic Role Of Inflammation In Hfmentioning
confidence: 99%
“…NYHA classification) and cardiac performance [i.e. left ventricular ejection fraction (LVEF)] [3,4,[7][8][9][10]18,19]. A series of experimental studies have revealed that the biological effects of cytokines may explain several aspects of the syndrome of chronic HF and the pathogenic role of inflammatory cytokines in HF is supported by various transgenic mouse models.…”
Section: Patho-genetic Role Of Inflammation In Hfmentioning
confidence: 99%
See 3 more Smart Citations